IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DI DESA SIBERUANG KECAMATAN KOTO KAMPAR HULU KABUPATEN KAMPAR TAHUN 2023 - Marent, Reyhan Baihaqi; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
The Family Hope Program is a program providing conditional social assistance to poor and vulnerable families registered in the Ministry of Social Affairs' integrated data on handling the poor. Whether or not this program is effective can be determined by the program management system. This study aims to (1) describe the implementation of the Family Hope Program in Siberuang Village, Koto Kampar Hulu District and (2) to determine the supporting and inhibiting factors faced by the organizers in implementing the Family Hope Program in Siberuang Village, Koto Kampar Hulu District. The approach used in this research is a qualitative descriptive approach. Respondents in this study were coordinators, assistants, and PKH participants. Data was collected through interview and documentation techniques. After the data is collected, it is then analyzed using Sheldon's qualitative analysis model. he conclusions obtained are: (1) The implementation of the PKH program at the planning, validation, determination of PKH KPM, data updating, mentoring, and monitoring and evaluation stages has been carried out in accordance with the PKH program implementation guidelines, while in the commitment verification element, not all members have shown a strong commitment because there are still PKH KPM who are not present if there are health services or routine meetings. (2) The supporting factors for the PKH program are: (a) The road infrastructure is quite good, (b) the telecommunications network is adequate, communication between the implementer and KPM is quite good, (c) assistance is received by the wife, (d) The ratio between companions and KPM members is quite proportional. Furthermore, the inhibiting factors found were (a) the commitment of PKH members is still low, (b) the understanding of PKH members regarding the PKH program is still relatively low, (c) the domicile of the companion does not match the work area, (d) PKH participants are dependent on assistance, (e) the PLN electricity supply often goes out, (f) the emergence of social jealousy, (g) KPM finds it difficult to coordinate with the bank, and (h) lack of support from the local government. Keywords: Implementation, Family Hope Program, Sibiruang Village